Al-Jazeera Sport's US Twitter followers: sport-politics nexus?. Issue 6 (10th October 2016) - Hayat, Tsahi; Samuel-Azran, Tal; Galily, Yair
Abstract : Purpose: The purpose of this paper is to contribute to analyses of the sport-politics nexus by identifying whether the demographics of Twitter followers of Al-Jazeera Sport in the USA (rebranded in 2014 as beIN USA) can be associated with a specific political orientation. Design/methodology/approach: Based on selective exposure theory, which posits that people follow news sources that reinforce their existing views, the authors identify the news outlets followed by beIN Twitter followers. To put the findings in perspective, the authors compared the results to the news outlets followed by the Twitter followers of Al-Jazeera America, Al-Jazeera's second US outlet. Next, to understand the nature of the beIN and Al-Jazeera America communities, the authors used social network analysis to analyze the distribution of retweets within these communities. Findings: The analysis shows that whereas Al-Jazeera America Twitter followers follow significantly more liberal than conservative news outlets, beIN's followers were not identified with a specific political orientation. Analysis of beIN's followers' retweets shows a greater degree of connectivity among beIN's followers than among the followers of Al-Jazeera America, indicating a more connected social network. Research limitations/implications: Findings indicate that beIN's Twitter following is characterized by more diverse and more strongly connected audience than Al-Jazeera America on Twitter, highlighting sports as a non-politicized realm on Twitter. Practical implications: For practitioners, the study illustrates that controversial non-western media networks such as Al-Jazeera can gain access to diverse populations in the West by operating in the sport realm rather than the news realm. Originality/value: This study offers a pioneering indication of the extent of a sport-ethnocentrism nexus on Twitter.